Reduplikasi Bahasa Dawan: Kajian Morfologis Distribusi - Rafael, Agnes Maria; Helenora Jem, Yosefina; Maharani, Sang Ayu Isnu (Universitas Ahmad Dahlan, 2023)
This article is intended to investigate the reduplication processes of bahasa Dawan spoken by Dawan people in NTT Province by using the morphological distribution theory proposed by Framton in 2004. To complete the study, a qualitative research method had been chosen based on the consideration that the data were in the form of words. Those data were taken from the utterances spoken in Dawan’s traditional ceremony as the main data source. Besides, Tata Bahasa Dawan book played a role as the secondary data source. The data were collected by observation and studying the document. In observation, the researchers observed and recorded the utterances by using an android, however the document study was done by reading documents about Bahasa Dawan. The study result reveals that in bahasa Dawab there are three processes in reduplication, namely 1) full reduplication without affixation process, 2) full reduplication with affixation process, and 3) partial reduplication.